Induction of Labour by Intravaginal Misoprostol In Intra Uterine Death of Fetus at Ssmc and Mitford Hospital, Dhaka (Journal of Dhaka Medical College, 2020)
Intra uterine fetal death occur in 1% of pregnancy. The patient goes into labour in most of the cases, spontaneously. Retained dead fetus may cause disseminated intravascular coagulation sometimes resulting death of a mother. Objective: The aim was to find out the reults after using intravaginal Misoprostol in Intrauterine fetal death in last trimester of pregnancy.Study design: This was a cross sectional observational study prospective in nature on 160 cases of intra uterine fetal death patients in indoor of department of Gynae and Obstertrics of Sir Salimullah medical college Hospital, Dhaka from 02/01/13 to 01/07/13, for a period of 6 months.Result: 60% of the patients were primi gravida. Mean age of the patients was 22.12±4.3 years 44% were in 33 to 36 weeks of pregnancy when induction was done. 41 (82%) patients having Bishops score d” 6 reqired 21±8.25 hours where as 09 (18%) patients having Bishops score e” 6 needed 10±1,1 hours to complete the delivery. There were no reports of maternal mortality. All the patients delivered per vaginally except one (2%) who needed ceasearean section due to development of chorioamnionitis.Conclusion: Intravaginal misoprostol can aid in vaginal delivery safely.J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 90-93